(untitled) (Impact: Journal of Transformation, 2026)
Nursing is a sensitive and stressful profession and employment of religious and spiritual coping strategies is necessary to mitigate work-family conflict. Nurses frequently navigate the tension between demanding professional responsibility and familial obligations, often leading to work-family conflict and emotional strain. This review explores how personal religious and spiritual beliefs serve as internal resources that enhance nurses’ well-being. Drawing from empirical studies, and theoretical perspectives, the paper highlights the protective role of spirituality in mitigating burnout and fostering resilience. These beliefs can provide a sense of purpose, support and reliance which can help mitigate work-family conflict. Moreover, the beliefs act as coping mechanisms, helping nurses manage the demands at work and at home. The paper presents an overview of how these beliefs foster a sense of inner peace and providing a framework for understanding and dealing with stressors due to their role in conflict resilience and emotional regulation. This enhances overall mental well-being and improve the ability to balance work and family demands. The paper demonstrates the need to have a clear policy and awareness for the healthcare staff to ensure that nurses make use of the services. The paper is important in informing healthcare facilities, churches, and Christian organizations to help nurses who are involved in this sensitive profession for better outcomes of not only quick recovery to the patients but for the well-being of the nurse’s family.